Contemporary Arab Broadcast Media - EL MUSTAPHA LAHLALI (Edinburgh University Press, 2011)
Before the war on Afghanistan in 2001, Arab media was almost unheard of; however, Al-Jazeera’s monopoly over the coverage of the war on Afghanistan has put Arab media on the map. While some people have struggled to grasp the reasons behind the long silence of the Arab media, others have shown a positive attitude towards the new development of media outlets in this turbulent part of the world. Since the independence of most of the Arab countries, the role of the media, both print and audio-visual, has been to safeguard Arabic culture and unity. This phase has witnessed tight control of the media by Arab regimes and governments. The Arab media’s main focus on matters of concern to the Arab public shifted because of various historical and economic changes that hit the region. During the 1970s and 1980s, the Arab media robustly defended the Palestinian theme and called for Arab unity and solidarity with the Palestinians. The regional main themes apart, Arab media has been utilised to promote governments’ domestic policies and the daily activities of governments and regimes. Media remains a potent weapon in the hands of governments to mobilise the public to support their policies. Today, the Arab world is undergoing a radical media change, featuring the launch of satellite and cable television channels. This has ended an era of state-controlled media and given way to privatisation. The inception of Al-Jazeera, Al-Hurra and Al-Arabiya are few examples to list here. These three channels have contributed immensely to generating an open, free and transparent debate on all matters of concern to the Arab public. Although these channels broadcast in the same language, Arabic, they have different sponsors, different aims and objectives, and different ideologies.